Quantitative Electroencephalographic Biomarkers in Preclinical and Human Studies of Huntington’s Disease: Are They Fit-for-Purpose for Treatment Development? - Leuchter, Michael K.; Donzis, Elissa J.; Cepeda, Carlos; Hunter, Aimee M.; Estrada-Sánchez, Ana María; Cook, Ian A.; Levine, Michael S.; Leuchter, Andrew F. (Frontiers in Neurology, 2017)
A major focus in development of novel therapies for Huntington’s Disease (HD) is identification of treatments that reduce the burden of mutant Huntingtin (mHTT) protein in the brain. In order to identify and test the efficacy of such therapies, it is essential to have biomarkers that are sensitive to the effects of mHTT on brain function to determine whether the intervention has been effective at preventing toxicity in target brain systems before onset of clinical symptoms. Ideally, such biomarkers should have a plausible physiologic basis for detecting the effects of mHTT, be measureable both in preclinical models and human studies, be practical to measure serially in clinical trials, and be reliably measurable in HD gene expansion carriers (HDGECs), among other features. Quantitative electroencephalography (qEEG) fulfills many of these basic criteria of a “fit-for-purpose” biomarker. qEEG measures brain oscillatory activity that is regulated by the brain structures that are affected by mHTT in premanifest and early symptom individuals. The technology is practical to implement in the laboratory and is well tolerated by humans in clinical trials. The biomarkers are measureable across animal models and humans, with findings that appear to be detectable in HDGECs and translate across species. We review here the literature on recent developments in both preclinical and human studies of the use of qEEG biomarkers in HD, and the evidence for their usefulness as biomarkers to help guide development of novel mHTT lowering treatments.